EFISIENSI PENATAUSAHAAN BARANG MILIK DAERAH (STUDI PADA PEMERINTAH KABUPATEN GAYO LUES) - , FAUDUZZAKIAH, Prof. Tri Widodo, S.E, M.Ec.Dev., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Administration of regional government property is a part of asset management system which needed in orderly administration and orderly management of regional assets. By implementing the administration in accordance with the applicable regulations, the value of regional assets, ownership, utilization and maintenance of regional assets will be known, so there will be synchronization between the local government financial reports and the regional asset reports. This study aims to analyze the efficiency level of regional assets administration in the Local Work Units (Satuan Kerja Perangkat Daerah/SKPD) Gayo Lues District Government by using Data Envelopment Analysis (DEA), whereas multiple regression was used to analyze the factors that affect the performance of the assets management. The results of the study by using Data Envelopment Analysis (DEA) with Constant Returns to Scale (CRS) assumption shows the relative efficiency values varied from 19.28 percent to 100 percent with average efficiency value of 51.78 percent, whereas Variable Returns to Scale (VRS) assumption, shows the relative efficiency values varied from 56.21 percent to 100 percent with average efficiency value of 93,91 percent. Multiple regression analysis showed that age, sex, and training has a positive and significant effect on the performance of SKPDâs assets management.